Pendampingan Pengelolaan Keuangan Dan Digital Marketing Pada Pelaku UMKM Sriti Gamplong - Rico Firmansyah; Ika Wulandari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This financial management and digital marketing assistance aims to provide knowledge of financial often experienced by UMKM entrepreneurs is ineffective financial management, and a lack of knowledge causes poor business performance. Not only that, but weak digital marketing knowledge is also a problem that is lacking in UMKM entrepreneurs. Therefore, it is necessary to have training and mentoring activities for financial management and digital marketing for local UMKM entrepreneurs. The implementation of this activity was carried out from July 24, 2023, to August 8, 2023. This activity was attended by two UMKM entrepreneurs. The methods the team used were counseling and mentoring. The results of this activity can increase knowledge and financial management, both properly and professionally.